Fuzzy logic controller for closed loop cascaded flyback converter fed PMDC-motor system - C.T. Manikandan; G.T. Sundarrajan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper displays a Fly Back Converter idea to straightforwardly incorporate cascaded flyback converter. The flyback-converter finds a way between DC-source and DC Motor-load. This work covenants with the modeling, simulation, and application of a Fuzzy Logic controlled (FLC) - Cascaded Fly back Converter (CFLB) system. This work recommends FLC to control Parallel cascaded fly-back converter to fabricate essential DC voltage from the input supply voltage. The yield of CFLB is controlled utilizing closed loop configuration. Closed loop PI & Fuzzy logic controlled CFLB systems are simulated and their results are related. The outcomes signify that the FLC based system gave a superior response than the P.I. controlled CFLB system. The FLC controlled CFLB system has benefits like decreased steady state error and enhanced time domain-response.